Investigations on Mechanical Strength and Microstructure of Multi-Pass Welded S690QL HSLA Steel Using MAG and FCAW - Mert, T.; Tumer, M.; Kerimak, Z. M. (WALTER DE GRUYTER GMBH, 2019)
High strength low alloy (HSLA) steels are quite crucial in weight reduction in manufacturing of vehicles and constructions with high steel thickness. Quenched and tempered S690QL HSLA steel with 700 MPa yield strength was multi-pass welded with 7 passes using MAG (Metal Active Gas) and FCAW (Flux Cored Arc Welding) methods. Heat inputs for both methods were tried to keep close to each other as much as the process parameters allowed. The effects of the welding wires and the process parameters for both methods on weld metals and heat affected zones (HAZ) were investigated. Weld metals, which were deposited by solid and cored wire electrodes, were subjected to mechanical tests and their toughness values were measured with Charphy V-notch impact test and analyzed using optical and SEM micrographs. Inclusions were present for both weld metals and HAZs. Inclusions were spherical oxides of Si, Mn and Ti for the FCAW specimen. The main microstructures of weld metals for both processes were acicular ferrite accompanied by grain boundary ferrite (GBF) and ferrite side plate (FSP) for MAG and GBF for FCAW. In coarse grain heat affected zone (CGHAZ) FCAWed specimens formed lath type martensite, which contributed to higher impact toughness compared with MAG specimens.
Keywords: COOLING RATE; TRANSFORMATION; FERRITE; NUCLEATION; INCLUSIONS; Metallurgy & Metallurgical Engineering